Reactive power control strategy for integrated photovoltaic inverter - Muhammad Ehtesham; Muhammad Junaid (Institute of Advanced Engineering and Science, 2022)
Rising penetration of photovoltaic (PV) power also poses several threats to electrical system which demands proper inverter control schemes to be designed. One major issue is that as PV systems are inherently non-inertial in nature, they do not participate in regulating voltage or reactive power and hence become highly sensitive to external disturbances. Any perturbation in voltage or frequency may cause some serious consequences in terms of loss of transient stability and reliability. Thus controlling the PV inverter for smooth operation of system while interfacing with grid brings a challenging task of maintaining both voltage and frequency well within the acceptable limits. Another important aspect is intermittency in PV output which demands application of some advance tracking algorithms. Therefore, novel control strategies for PV interfacing have been presented in this paper. The proposed synchroconverter based inverter controller enables the system to inject both active and reactive powers and facilitates the integrated PV system to withstand voltage or frequency perturbation. Whereas an enhanced control algorithm is applied here that can estimate panel parameters precisely offering effective tracking for any conditional variance. Proposed synchroconverter based controllers have been analyzed through simulations for different spans of time according to voltage and frequency variations.